Avaliação de processos erosivos intensos no núcleo de desertificação de Gilbués-PI - Simplício, Antonio Álisson Fernandes (2020)
With an area of 6,200 km², the Gilbués badlands region in Brazilian drylands is the largest desertification site in the country. It is located upstream the Boa Esperança Hydroelectric Power Plant and contiguous to an important Brazilian agricultural area. However, primary quantitative data on erosive processes are scarce or inexistent. We analyzed on-site data (2018 – 2019) concerning small-scale (hillslope and micro basin) processes: interrill gross erosion, vegetation coverage factor, sediment yield, and sediment delivery ratio. We measured gross erosion in four hillslopes using metal pins; rainfall erosivity using an automatic meteorological station; soil erodibility; and siltation of five check dams that control micro basins (10¹–10³ m²) by means of an unmanned aerial vehicle. Gross erosion (10² Mg.ha-¹.yr-¹) is up to 100-fold the regional mean value and up to 45 times the tolerable soil-loss reference value, showing that degradation still evolves. Sparse small vegetation directly exposes two thirds of the soil, with a high vegetation factor (0.90). The sediment delivery ratio of the micro basins is 0.88, compatible with low (12%) sediment-deposition pattern at this scale. Maner delivery-ratio model mimicked field observation, which indicates that relief is the key element influencing sediment deposition there. The check-dam effectiveness considerably decreased after the first decade of operation due to high siltation rates. Although the Gilbués badland occupies only 5% of a basin upstream the power plant, it contributes with 32% to its sediment load. This shows the relevance of the badland restoration for the regional sustainability of water and energy supply.